1992
DOI: 10.1111/j.1600-0714.1992.tb00967.x
|View full text |Cite
|
Sign up to set email alerts
|

Odontogenic lesions in opercula of permanent molars delayed in eruption

Abstract: Opercula of permanent first and second molars delayed in eruption were investigated histologically to detect possible causes of eruption failure. The material comprised operation specimens from exposure of 74 non-erupted molars in 63 young individuals (34 boys, 29 girls). Eighteen of the 74 specimens (or 24.3%) were diagnosed as "classical" odontogenic tumors belonging to the following entities: ameloblastic fibroma (seven), ameloblastic fibrodentinoma (six), ameloblastic fibro-odontoma (four) and complex odon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 6 publications
1
29
0
Order By: Relevance
“…Multinucleated giant cells with a fibroblast-like shape have previously been found in the connective tissue covering teeth delayed in eruption (Onishi et al, 2003;Philipsen et al, 1992;Yonemochi et al, 1998), in the retrocuspid papilla (Buchner et al, 1990), and in cutaneous giant cell collagenomas, where they were notably associated with mast cells (Ramos et al, 2002). The ultrastructural features confirmed that the multinucleated cells of opercula were giant cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Multinucleated giant cells with a fibroblast-like shape have previously been found in the connective tissue covering teeth delayed in eruption (Onishi et al, 2003;Philipsen et al, 1992;Yonemochi et al, 1998), in the retrocuspid papilla (Buchner et al, 1990), and in cutaneous giant cell collagenomas, where they were notably associated with mast cells (Ramos et al, 2002). The ultrastructural features confirmed that the multinucleated cells of opercula were giant cells.…”
Section: Discussionsupporting
confidence: 57%
“…Odontogenic epithelium has previously been noted particularly in opercula of teeth delayed in eruption (Gardner and Radden, 1995;Gomez et al, 1998;Lukinmaa et al, 1990;Philipsen et al, 1992;Sandler et al, 1988;Yonemochi et al, 1998). As erupting teeth are usually covered with the reduced enamel epithelium derived from the antecedent dental lamina, the presence of epithelial rests in normal opercula is not surprising.…”
Section: Discussionmentioning
confidence: 92%
“…Maxillary first molars were present in almost all patients with non-syndromic hypodontia who were missing several other teeth [15,16]. For its part, it is always studied delayed eruption of tooth and eruption disorder of the maxillary first molar [17][18][19]. Conversely, reports of patients missing only the maxillary first molar have also been published [5,[20][21][22].…”
Section: Introductionmentioning
confidence: 98%
“…The association is seen with the opercula of the unerupted or delayed erupted second and third molars [6,7] . Previous literature has reported lesions like odontogenic giant cell fibromatosis (OGCF) and Abhishek B et al Odontogenic hamartomas 493 peripheral myxofibrous hyperplasia (PMH) [8] .…”
Section: P E R I C O R O N a L H A M A R T O M A T O U S Lesions (Phls)mentioning
confidence: 99%
“…The etiology of the peripheral odontogenic fibroma whether reactive or hamartomatous is always debatable. The significant recurrence of the lesion suggests its neoplastic character and the lack of giant cells in the histopathology suggest that PHLs are unique as an entity [7] .…”
Section: P E R I C O R O N a L H A M A R T O M A T O U S Lesions (Phls)mentioning
confidence: 99%